Analysis of changes in the hydrological regime in Lalin River basin and its impact on the ecological environment - Wang, Xuege; Ma, Wenchao; Lv, Jun; Li, Hongyan; Liu, Hongchao; Mu, Guangyi; Bian, Dejun (Frontiers in Earth Science, 2022)
Lalin River is a first-level tributary of the right bank of Songhua River. High-quality corn production bases irrigated by the Lalin River are famous throughout the country. However, in the last few decades, the hydrological regimes changed severely due to expansion of the irrigation area, leading to more water used for irrigation. To investigate the variation of the hydrological situation, we analyzed the daily runoff data at the Caijiagou Hydrological Station from 1954 to 2015 by using the Indicators of Hydrologic Alteration (IHA) and the range of variability approach (RVA). The results showed a severe decreasing trend of the average monthly flow during the water level with regular and high periods, with a negative slope of −2.924 in August and −2.518 in September. The increasing trend of low pulse and fall rate of flow and the decreasing trend of the rising rate of flow demonstrate that water resources are drying up. Regarding the flow rate, the annual maximum value decreased significantly in slopes of −7.9, −7.6, −6.09, −5.28, and −2.98 on the 1-day, 3-day, 7-day, 30-day, and 90-day, respectively. The flow reversals’ average value is 65 to 50 times/year from 1954 to 2015. From RVA analysis, the hydrological alteration of the basin decreased 50% after 1978. To investigate the influencing factors for the hydrological alteration, we analyzed the variation in land cover and land use between 1978 and 2015. The results showed that the area of paddy fields in 2015 was 1.5 times that of 1978, and the water consumption in paddy fields accounts for 80.8% of the total water resources. Consequently, the wetland area of the basin in 2015 was only 53% of 1978, and the wetland area of the two wetland nature reserves at the mouth of the Lalin River in 2015 was about 53% of 1978. Furthermore, the meteorological condition in the LRB shows a warming and drying tendency. The air temperature has shown an intensively increased tendency, and precipitation decreased in the last 50 years. This indicates that the hydrological situation in the Lalin River Basin has changed considerably under the dual influence of human activities and global warming.